Barangay chairperson’s competence of oral communication skills in resolving conflicts in the Philippines - Jacinto, Ashley; Diamante, Larhraineil Aleina; Tamano, Analeah; Abrahan, Rinzie; Nacionales, Joseph; Claridad, Norberto (Yayasan Mitra Persada Nusantara, 2023)
Peace and order in the community may give its citizens harmonious living conditions but achieving them requires the cooperation of every member of the community as well as the government's implementation of effective policies and programs. Without these, conflicts and disagreements among community members may arise for an array of reasons. These conflicts can lead to negative consequences such as decreased productivity, loss of trust, and even violence. Hence, it is important to understand the root causes of conflicts and implement effective conflict resolution strategies to promote harmony and cooperation within the community. However, communities either do not have the trained personnel needed to properly manage conflicts or lack the necessary knowledge themselves, such as the use of communication skills for resolving conflicts is a problem. Hence, the main purpose of this study is to explore the competence of barangay chairpersons in the Philippines in using oral communication skills to resolve conflicts within their communities. The study adapted the qualitative research design using interpretative phenomenological analysis (IPA) as the specific method. A total of eight (8) participants (3 females and 5 males) via purposive-convenience sampling were catered. After the data gathering using a semi-structured interview, findings revealed that some have confidence in their competence, but others still need improvement. Furthermore, some participants were able to solve majority of the conflicts arises at their vicinities. On the other hand, the participants used a wide variety of skills that helped to effectively resolved conflicts in their barangay and communication skills were commonly used by them.